Menjadi Manusia Indonesia yang Otentik: Belajar dari Hans Kung - Andreas Maurenis Putra (Societas Dei: Jurnal Agama dan Masyarakat, 2019)
Abstract: Globalization has a significant impact on the dynamics of human life. The activities and creativities of individuals in society are facilitated. Everyone's knowledge and relations are increasingly widespread. Humans are becoming increasingly compliant in various dimensions: space and time. The cool breeze brought by modernity refreshes the external needs of personal and communal life. But the cool breeze of modernity inevitably lulls the deepest elements of life. Humans must be treated humanly, experiencing lameness. This dimension is blurred because it is rarely criticized because the society, both globally (world) and locally (Indonesia) is lulled by the pleasures of modernity. In the light of Hans Kung's thought, the perspectives in this discourse affirm the commitment to realize human authenticity in general, in a global context and implementation into the local domain, our Indonesian. The ideas presented in this thesis frame -more less- a fundamental problem experienced by modern humans and the possibility of anticipation in the future so that the hope of realizing authentic human beings as outward and spiritual in nature, will not lost eroded and carried away by globalization. keywords:Globalization, Fundamental Demands, Authentication, Commitment, Implementation, Spirit of Pancasila Abstrak: Globalisasi membawa dampak signifikan dalam dinamika hidup manusia. Aktivitas dan kreativitas individu dalam masyarakat dipermudah. Wawasan dan relasi setiap orang semakin meluas. Manusia menjadi semakin kompeten dalam berbagai dimensi: ruang dan waktu. Angin sejuk yang dibawa modernitas menyegarkan kembali kebutuhan-kebutuhan luaran hidup pribadi dan kelompok. Namun sejuknya angin modernitas tak pelak meninabobokan unsur terdalam kehidupan. Manusia harus diperlakukan secara manusia, mengalami kepincangan. Dimensi ini menjadi kabur lantaran jarang dikritisi karena masyarakat, baik secara global (dunia) maupun lokal (Indonesia) terlena oleh nikmatnya tawaran-tawaran modernitas. Dalam terang pemikiran Hans Kung, perspektif-perspektif dalam diskursus ini memberi penegasan pada komitmen mewujudkan otentisasi manusia secara umum dalam konteks global dan implementasi ke ranah lokal, keindonesian kita. Ide-ide yang tersaji di dalam tesis ini membingkai--kurang lebih--apa yang menjadi persoalan fundamental yang dialami manusia-manusia modern dan kemungkinan antisipasi ke depannya sehingga harapan merealisasikan manusia-manusia yang otentik sebagaimana hakikat lahiriah dan spiritual, tidak hilang tergerus dan terbawa arus globalisasi.Kata-kata kunci: Globalisasi, Tuntutan Fundamental, Otentisasi, Komitmen, Implementasi, Semangat Pancasila.